Public-private partnerships for the circular bio-economy in the Global South: lessons learned - Taron, Avinandan; Majumder, A.; Bodach, Susanne; Agbefu, Dzifa (International Water Management Institute, 2023)
Processing biomass from different waste streams into marketable products such as organic fertilizer and bio-energy is increasingly realized through public-private partnerships (PPPs). In developing countries, the private sector can be expected to contribute technical skills, organizational capabilities and marketing expertise, and leverage capital inflow. In contrast, the public sector will provide the regulatory framework and help its enforcement, plan public investment, involve and educate stakeholders, and ensure waste supply. This report reviews case studies that implemented PPPs in resource recovery and reuse (RRR) from waste streams with a particular focus on Asia and Africa, including those PPPs facilitated by the authors. Critical factors behind the success and failure of these cases are analyzed. The review indicates three key barriers to success: (i) waste-related bottlenecks, (ii) limited awareness about RRR products and their market(ing), and (iii) lack of proper institutional frameworks. Common shortfalls concern failure to meet commitments related to the quality and quantity of waste, missing understanding of the reuse market, etc. The report points out mitigation measures addressing possible challenges around appropriate technologies, finance and revenue streams, legal issues, as well as social and environmental concerns. It is required to establish close monitoring, appropriate procurement mechanisms and due diligence during the project preparation and pre-bid. If possible, such a PPP project should consider risk and commercial viability assessment as well as financial strategy planning (scaling). Successful involvement of the private sector in the RRR market is critical to close the resource loop and safeguard human and environmental health, which is the overarching objective of sustainable waste management.